(untitled) (International Journal of Engineering and Computer Science, 2015)
In this paper, I will propose and analyze binary ZCD (zero correlation duration) code and PN (pseudonoise) codes of ultra wide band (UWB) systems for wireless body area network (WBAN). In wireless body area network, there are many types of wireless communication devices on a human body, multiple access interference (MAI) can occur. Systems with less MAI effect have more efficiency and less harmful effect. The performance is checked and resulted in terms of BER (bit error rate) of UWB system for different devices in WBAN channel and different length of ZCD and PN (pseudonoise) codes. Firstly for two devices(one with ZCD code and one with PN code) and then for three devices. From simulation results, it is confirmed that the UWB system with the ZCD code achieves better performance compared with that of (PN) code.